Effect of “Time To Surgery” on the Endometrial Cancer Prognosis - Engin Celik; Harika Yumru Celiksoy; Hamdullah Sozen; Hale Goksever Celik; Semen Onder; Mehmet Yavuz Salihoglu; Samet Topuz (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: Endometrial cancer is the most common gynecological cancer in developed countries. Our study aims to determine the effect of the time between diagnosis and surgery of endometrial cancer on the prognosis of the disease.